A General Strategy for Development of Activatable NIR‐II Fluorescent Probes for In Vivo High‐Contrast Bioimaging. Issue 2 (3rd November 2020) - Ren, Tian‐Bing; Wang, Zhi‐Yao; Xiang, Zhen; Lu, Peng; Lai, Huan‐Hua; Yuan, Lin; Zhang, Xiao‐Bing; Tan, Weihong
Abstract: Organic dye based NIR‐II fluorescent probes, owing to their high signal‐to‐background ratio and deeper penetration, are highly useful for deep‐tissue high‐contrast imaging in vivo. However, it is still a challenge to design activatable NIR‐II fluorescent probes. Here, a novel class of polymethine dyes (NIRII‐RTs), with bright (quantum yield up to 2.03 %), stable, and anti‐solvent quenching NIR‐II emission, together with large Stokes shifts, was designed. Significantly, the novel NIR‐II dyes NIRII‐RT3 and NIRII‐RT4, equipped with a carboxylic acid group, can serve as effective NIR‐II platforms for the design of activatable bioimaging probes with high contrast. As a proof of concept, a series of target‐activatable NIRII‐RT probes (NIRII‐RT‐pH, NIRII‐RT‐ATP and NIRII‐RT‐Hg) for pH, adenosine triphosphate (ATP), and metal‐ion detection, were synthesized. By applying the NIRII‐RT probe, the real‐time monitoring of drug‐induced hepatotoxicity was realized. Abstract : The presented work reports a new class of polymethine dyes (NIRII‐RTs) with bright, stable, and anti‐quenching NIR‐II emissions together with large Stokes shifts. Importantly, by introducing the carboxylic acid functional group, the novel dyes NIRII‐RT3 and NIRII‐RT4 can serve as effective NIR‐II platforms for the design of activatable bioimaging probes with high contrast.